2012
DOI: 10.1188/12.onf.278-286
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Breast Cancer Survivors: The Impact of a Mind-Body Medicine Intervention

Abstract: Nurses and other healthcare team members can effectively impact persistent fatigue in breast cancer survivors through the use of a multipronged MBM program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…This revision to the protocol was deemed necessary in response to participant suggestions from the previous three rounds who regarded the 8-week intervention timeline as too cumbersome. This compressed program was previously pilot-tested and found to be associated with a similar reduction in fatigue levels as noted in the 8-week program (Appling et al, 2012).…”
Section: Description Of Interventionsupporting
confidence: 66%
See 3 more Smart Citations
“…This revision to the protocol was deemed necessary in response to participant suggestions from the previous three rounds who regarded the 8-week intervention timeline as too cumbersome. This compressed program was previously pilot-tested and found to be associated with a similar reduction in fatigue levels as noted in the 8-week program (Appling et al, 2012).…”
Section: Description Of Interventionsupporting
confidence: 66%
“…This qualitative study is part of a larger mixed-method investigation of an evidence-based multimodal group program for breast cancer survivors experiencing fatigue (Appling et al, 2012). We build from the previously reported quantitative findings by using qualitative data collection methods to capture the experience of adding a family component to the intervention.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…2,4 It has been reported that 48% to 83% of breast cancer patients or survivors turn to complementary therapies (eg, mind-body exercise and herbal therapy), which they believe can assist them in managing the side effects of conventional cancer treatments such as persistent fatigue and hence improve their quality of life. [5][6][7] Among these complementary therapies, qigong exercise is a rather popular self-help means of relieving the signs and symptoms related to conventional cancer treatments. Qigong is a mind-body integrative exercise originating from traditional Chinese medicine and is used to improve health and energy levels through regular training.…”
Section: Introductionmentioning
confidence: 99%